The predictive value of the ARC-HBR criteria for in-hospital bleeding risk following percutaneous coronary intervention in patients with acute coronary syndrome - Juan Liu; Hui He; Hong Su; Jun Hou; Yan Luo; Qiang Chen; Qiao Feng; Xiufen Peng; Maoling Jiang; Long Xia; Hanxiong Liu; Zhen Zhang; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: The Academic Research Consortium for High Bleeding Risk (ARC-HBR) criteria were proposed for predicting bleeding risk in patients undergoing percutaneous coronary intervention (PCI). However, there is a lack of research evaluating the risk of in-hospital bleeding following PCI for acute coronary syndrome (ACS) utilizing the ARC-HBR criteria. Methods and results: This study involved 1013 ACS patients who underwent PCI and dual antiplatelet therapy. There were 63 cases of in-hospital bleeding events (6.22 %). According to the ARC-HBR criteria, patients classified as HBR had a significantly greater bleeding rate than non-HBR patients (15.81 % vs. 1.99 %, p < 0.001). As the CRUSADE score category increased, the risk of bleeding also increased. The area under the receiver operating characteristic curve (AUC) of the ARC-HBR criteria was significantly greater than that of the CRUSADE score for bleeding (0.751 vs. 0.696, p < 0.0001). Subgroup analysis revealed that the ARC-HBR criteria exhibited better predictive ability for ST-segment elevation myocardial infarction (STEMI, AUC 0.767 vs. 0.694, p = 0.020) but comparable predictive ability in patients with unstable angina (AUC 0.756 vs. 0.644, p = 0.213), non-ST-segment elevation myocardial infarction (AUC 0.713 vs. 0.683, p = 0.644), and non-ST-segment elevation ACS (AUC 0.739 vs. 0.687, p = 0.330). Conclusion: Compared with the CRUSADE score, the ARC-HBR criteria demonstrate superior predictive ability for in-hospital bleeding events during PCI in ACS patients. Routine assessment of the ARC-HBR score might be helpful for identifying high-risk individuals in this specific population.